Ferroptosis, M6A and immune checkpoint-related gene expression in the middle temporal gyrus of the Alzheimer's disease brain - Qinfeng Liu; Fan Yang; Sijia Wu; Kai Yuan; Liyu Huang; Suping Cai (Meta-Radiology)
Alzheimer's disease (AD) is a common genetically related cognitive disorder. Studies have shown that ferroptosis, N⁶-Methyladenosine (M6A) and immune checkpoint are related to the development of AD. However, the effects of these three gene pathways on AD progression are still unclear. Here, we used genes expressed in the middle temporal gyrus (MTG) to study the differences in ferroptosis, M6A and immune checkpoint-related gene in 97 Alzheimer's disease and 98 normal controls (NC). We then conducted correlation analysis between ferroptosis, M6A and immune checkpoint-related gene expression levels to investigate the relationship between these genes and AD. Compared to the NC, the gene expression from MTG in AD are as follows: (1) in ferroptosis related genes, the expression of CARS, CDKN1A, HSPB1, MT1G, EMC2, SAT1 and SLC1A5 was increased, while the expression of ACSL4, ATP5MC3, CSID1, CS, DPP4, GLS2 and GPX4 was decreased; (2) in M6A-related genes, the expression of HNRNPA2B1, IGF2BP2, RBM15B and YTHDC1 was increased, while the expression of FTO, YTHDC2 and YTHDF2 was decreased; (3) the expression of immune checkpoint-related genes (including CTLA4, HAVCR2 and LAG3) was increased. Further, we determined related gene pathways among these genes by conducting a literature review. By verifying the dataset, we can well verify our results and prove that our results have good robustness. We concluded of gene expression that a complete set of ferroptosis, M6A and immune checkpoint regulatory mechanisms is activated in the MTG during AD development.